INTEGRATING SUSTAINABILITY INTO ERP SYSTEMS - Popova, Diana (E-Journal VFU, 2025)
The article examines the significance of ERP systems as a strategic platform for sustainability management (ESG). The analysis begins by defining sustainability as a holistic imperative that transcends the traditional focus on profit. It is established that traditional accounting information, managed by ERP, is insufficient for measuring ESG factors and long-term value. Mechanisms through which ERP must be adapted are explored – namely, by expanding management accounting and integrating non-financial metrics into operational modules. Through Business Intelligence (BI) and DSS, the integrated ERP transforms raw data into strategic options. This supports complex management decision-making, such as the optimization of the supply chain based on ecological criteria and the provision of a reliable basis for integrated reporting.
Keywords: ERP systems; Sustainability; Accounting information; Business Intelligence (BI)